2007
DOI: 10.1111/j.1365-2893.2007.00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term lamivudine treatment of children with chronic hepatitis B: durability of therapeutic responses and safety

Abstract: SUMMARY. Lamivudine has been demonstrated safe and efficacious in the short term in a large cohort of children with chronic hepatitis B (CHB), but optimal duration of treatment has not been elucidated and limited data on the safety of long-term lamivudine administration have been reported. In addition, the durability of favourable therapeutic outcomes after lamivudine therapy in children has not been well characterized. The aim of this study was to examine the safety of lamivudine and the durability of clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 14 publications
0
36
0
1
Order By: Relevance
“…Studies using conventional IFN-a have demonstrated increases in the rate of HBsAg and HBeAg loss, but most of the children suffered from adverse events, such as hair loss and changes in personality [101]. LAM was safe when given to children and induced HBeAg loss in almost a fifth of them, but continuous treatment resulted in the development of tyrosine-methionineaspartate-aspartate (YMDD) mutants (19-24% after 1 year, 49-59% after 2 years and 64% after 3 years of treatment) [102]. However, 82% and >90% of the children who lost HBeAg and were treated with LAM for 52 weeks and for at least 2 years consequently, remained HBeAg -for at least 2 years after treatment cessation [102].…”
Section: Children With Chronic Hepatitis Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using conventional IFN-a have demonstrated increases in the rate of HBsAg and HBeAg loss, but most of the children suffered from adverse events, such as hair loss and changes in personality [101]. LAM was safe when given to children and induced HBeAg loss in almost a fifth of them, but continuous treatment resulted in the development of tyrosine-methionineaspartate-aspartate (YMDD) mutants (19-24% after 1 year, 49-59% after 2 years and 64% after 3 years of treatment) [102]. However, 82% and >90% of the children who lost HBeAg and were treated with LAM for 52 weeks and for at least 2 years consequently, remained HBeAg -for at least 2 years after treatment cessation [102].…”
Section: Children With Chronic Hepatitis Bmentioning
confidence: 99%
“…LAM was safe when given to children and induced HBeAg loss in almost a fifth of them, but continuous treatment resulted in the development of tyrosine-methionineaspartate-aspartate (YMDD) mutants (19-24% after 1 year, 49-59% after 2 years and 64% after 3 years of treatment) [102]. However, 82% and >90% of the children who lost HBeAg and were treated with LAM for 52 weeks and for at least 2 years consequently, remained HBeAg -for at least 2 years after treatment cessation [102]. Moreover, adefovir given for 48 weeks to children 2-17 years of age had similarly good results, which were better in the group of children older than 12 years [103].…”
Section: Children With Chronic Hepatitis Bmentioning
confidence: 99%
“…In the study of Kuloğlu et al (21), it was stated that treatment with lamivudine for a mean period of 18 months would be sufficient. Jonas et al (22) showed that lamivudine could be used safely up to three years. Genetic study directed to lamivudine resistance was not performed in any of the patients who did not give response to lamivudine treatment.…”
mentioning
confidence: 99%
“…This treatment, however, has significant side effects, including flu-like symptoms, neutropenia, nausea, and psychiatric effects. Use of nucleoside and nucleotide analogues, while effective in viral suppression, is associated with development of viral resistance and return of detectable HBV over time (3,(5)(6)(7).…”
mentioning
confidence: 99%
“…This treatment, however, has significant side effects, including flu-like symptoms, neutropenia, nausea, and psychiatric effects. Use of nucleoside and nucleotide analogues, while effective in viral suppression, is associated with development of viral resistance and return of detectable HBV over time (3,(5)(6)(7).Telbivudine (LDT600, Sebivo, Tyzeka) is the unmodified Lenantiomer of the naturally occurring nucleoside thymidine and has been approved for the treatment of chronic HBV infection in adults. In the phase III GLOBE study of 1,370 patients Ն16 years of age, treatment with telbivudine (600 mg/day) for 52 weeks resulted in undetectable serum HBV DNA levels in 60% of HBeAgpositive and 88.3% of HBeAg-negative patients; lamivudine (100 mg/day) treatment achieved the same response in 40.4% and 71.4% of each group, respectively (8).…”
mentioning
confidence: 99%